FORMATION OF THE MUSICAL CULTURE OF THE STUDENTS WITHIN THE PROGRAM "SPIRITUAL SURVIVAL"( RUKHANI ZHANGYRU) - Akbuzhurova, S.Zh.; Amirkhamzin, N.К.; Esmaganbetova, Sh.К.; Serzhan-Abdrakhmanova, Sh.K. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
The article deals with the processes related to the modernization and the State Program «RUKHANI ZHANGYRU» the formation of the musical culture of university students. Contributing to the formation of a world of spiritual values of the younger generation, ideas about musical traditions, patriotism and diligence, respect for the individual. Interest in local musical culture, classical music, folk music traditions.
Keywords: formation of musical culture of university students; raining of specialists; higher education system; spiritual values; young generation; traditions; classical music; folk music